2002
DOI: 10.1542/peds.109.2.e38
|View full text |Cite
|
Sign up to set email alerts
|

Cochleovestibular Impairment in Pediatric Cogan’s Syndrome

Abstract: ABSTRACT. Cogan's syndrome is a rare, chronic inflammatory disorder that typically targets the eyes and vestibuloauditory apparatus, but it may also involve other organs. Three pediatric cases of Cogan's syndrome (ages 5, 13, and 18 years) are reported with long-term follow-up and complete and regular cochleovestibular functional evaluation and ophthalmologic and neurologic examinations. One case was a typical form (characterized by an interstitial keratitis and cochleovestibular impairment), whereas the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…When hearing loss occurs, early steroid systemic treatment, (typically 1-2 mg/kg per day) reduces the risk of development of profound hearing loss [6,13] and leads to an improvement in 50% of cases as early as the first week [3]-which was the case for our patient. One major problem for patients with Cogan's syndrome is that despite a rapid and sometimes spectacular initial response to treatment, relapses are frequent when steroids are stopped or during the decrease of dosing.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…When hearing loss occurs, early steroid systemic treatment, (typically 1-2 mg/kg per day) reduces the risk of development of profound hearing loss [6,13] and leads to an improvement in 50% of cases as early as the first week [3]-which was the case for our patient. One major problem for patients with Cogan's syndrome is that despite a rapid and sometimes spectacular initial response to treatment, relapses are frequent when steroids are stopped or during the decrease of dosing.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the inflammatory lesions of the eye and ear, systemic symptoms are present in 50-70% of cases [5]. Early steroid treatment improves long term prognosis [6]. Standard management is oral prednisone at 1-2 mg/kg per day.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be due to vasculitis, ossicular involvement, neuritis or ototoxicity of the drugs used for the treatment of rheumatologic diseases (18). Thus, hearing loss may be seen in conductive, sensorineural or in mixed pattern in secondary AIED (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(19)(20). Özcan et al suggested middle ear involvement for the reason of hearing loss in RA (18).…”
Section: Discussionmentioning
confidence: 99%
“…Bununla birlikte, otoakustik emisyon (OAE) gibi diğer testleri de içeren ve daha büyük örneklem büyüklüğüne sahip başka çalışmalara da ihtiyaç vardır. (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The inner ear pathologies caused by these disorders are commonly mild and slowly progressive whereas primary AIED is characterized by sudden onset, commonly bilateral, fluctuant and progressive sensorineural hearing loss (SNHL) with accompanying vertigo in some occasions.…”
Section: öZetunclassified